Politique nationale de l’eau au Québec : constat et perspectives - Alexandre Brun; Frédéric Lasserre (VertigO)
The Quebec National Water Policy was designed at the beginning of the XXIst century, after a long development process initially triggered by a legal debate over the status of water. The policy aims at fostering a decentralized participation. At the provincial level, the State defines rules and objectives ; at the local level, basin-wide organizations are in charge of defining hydraulic planning and the implementation of improvement plans. However, to what extent is the process open and participative if municipalities remain the only actor responsible for territorial planning ? Besides, local water governance does not have yet any legitimacy with the local elected representatives. In the frame of the recent Act to affirm the collective nature of water resources and provide for increased water resource protection, this article analyzes the forces behind water policy in Quebec and suggests several solutions inferred from infield surveys. The article puts forth the usefulness of a soil waterproofing fee as well as the efficiency of a municipal-based water policy, which could prove an avenue given the administrative complexity of the basin-based approach.